Osteoblastoma: A Rare Cause of Stiff Elbow. Issue 1 (January 2013) - Spence, Stephanie; Gupta, Sanjay; Ritchie, David; MacDuff, Elaine; Rymaszewski, Lech; Mahendra, Ashish
Osteoblastoma is a benign, osseous tumour that is usually found in the femur, tibia, foot and posterior elements of the vertebrae but rarely around the elbow. Elbow stiffness is common after trauma, infection (in particular tuberculosis), synovitis and arthritis, but is rarely caused by a tumour. In this case, an osteoblastoma in the distal humerus was excised through an Outerbridge—Kashiwagi approach, which successfully addressed the patient's main complaint of elbow stiffness and restricted function. However, the lesion recurred a few months later and was treated successfully by computed tomography-guided thermoablation.